Proses Pembelajaran Pendidikan Kristen Anak Usia Dini Berbasis Hermeneutika: Membangun Pemahaman Iman Anak Sejak Dini (Pusat Riset dan Inovasi Nasional, 2026)
This study discusses the learning process of Christian Religious Education (CRE) for early childhood based on a hermeneutical approach as a pedagogical strategy for fostering children’s faith from an early age. Early childhood is a critical stage in faith development; therefore, learning methods must be not only informative but also transformative and meaningful. This study employs a qualitative method through a literature review, analyzing hermeneutical theories, early childhood development studies, and CRE teaching practices in the Indonesian educational context. The findings indicate that the application of child-centered hermeneutics enables teachers to connect biblical messages with children’s concrete experiences through storytelling, visual media, role-playing, and multisensory activities appropriate to children’s world. Contextual, simple, and creative interpretation of biblical texts helps children internalize faith values more deeply and practically. This study emphasizes the importance of strengthening teachers’ competencies through practical hermeneutics training and implementing developmentally appropriate learning approaches. Thus, hermeneutics functions not only as a tool for interpreting biblical texts but also as a pedagogical process that holistically shapes children’s faith development.